A PROBLEM OF OPENING OF THE SECOND FRONT IS IN EUROPE: LOOK AFTER SEVEN DECADES - A. A. Paderin (Vestnik MGIMO-Universiteta)
For the expired time of seventy years historiography of this comprehensive problem was enriched with a large number of researches in our country and in western countries. The author associate himself with those historians, who support the origin of idea about the efficient strategy of attack against enemy simultaneously from different directions by the defeat of Germany, against which in the years of world war first two-front war was going: Russian army - from the east and Anglo-Franco-American soldiers from the west. The concept «second front» in its modern meaning, as it was suggested in the article, came into use widely since 1941 due to the beginning of German aggression against the USSR. In author's opinion, it is fully grounded historically, that front, formed by the Anglo-American troops in Normandy, for example, was called not norman or western, but «second». As it is generally known, to the summer of 1944 western allies have already conducted battle actions in North Africa, Italy, on the Pacific Ocean and in South-east Asia. Moreover, in war process their activity in battles with enemy increased both in the air, and at the seaside. However, as author shows, the USSR decision-makers persevering defended the other way, leading to more rapid victory over an aggressor - to the opening by allies of the second front in Europe. Both for the western politicians and for the allied command armies it was abundantly clear, but for Anglo-American decision-makers such choice was unacceptable. The article deals with the view of the reasons of such position of allies. Thus, an author relies not only on the results of his personal study of a problem but also onto a large extent of researches both domestic and foreign historians. Therefore he answers on the row of concrete questions, such as Why did the second front in Europe became reality only on the fifth year of Second world war? What led soviet government to strive so persistently for its fastest opening? What underplots of western allies did determine their attitude toward the problem of opening of the second front?